Acute Viral Encephalitis - Ekram, ARM Saifuddin; Hossain, Md J; Hussain, Sultana M; Alam, Md M; Hossain, SMA; Ahmed, I; Rahman, Md F; Begum, SMK Nahar; Gurley, E; Brieman, Robert F (TAJ: Journal of Teachers Association, 2009)
Viral encephalitis remains a significant public health problem world wide including Bangladesh. Its transmission is either from insect or environmental vectors or from human-to-human contact. Cerebrospinal fluid analysis, viral studies, and various imaging techniques provide sensitive and specific methods to detect many of these viral pathogens. Rapid diagnosis of encephalitis allows early intervention in those conditions that are responsive to specific antiviral treatment, such as herpes simplex encephalitis. Specific treatment is available for certain viral encephalitides, but for others only supportive therapy is available. Vaccines are available to prevent a few important causes of encephalitis, but prevention of encephalitis revolves around minimizing exposure to pathogens, and insects which transmit many of them. Control must be based on rapid recognition of early cases, subsequent immunization of persons or animals at risk, or immunization of persons or animals with the potential to be at risk, such as travelers, laboratory personnel, and attending clinicians. doi: 10.3329/taj.v16i1.3902 TAJ June 2003; Vol.16(1): 32-38